Traumatic Social Events and Their Influence on Depression Among Adolescent Mothers in Public Secondary Schools in Turbo Sub- County, Kenya - Janet Jepchirchir Kosgei (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
Depression among adolescent mothers is a significant mental health concern, particularly in socio-economically disadvantaged settings. This study examined the influence of traumatic social events on depression among adolescent mothers in public secondary schools in Turbo Sub-County, Kenya. Guided by Beck and Bredemeier’s Unified Model of Depression and Bronfenbrenner’s Ecological Systems Theory, the study adopted a cross-sectional survey research design involving 169 adolescent mothers aged 10–19 and guidance and counselling teachers. Data were collected using the Patient Health Questionnaire-9 (PHQ-9), a structured questionnaire, and interview schedules. Quantitative data were analysed using descriptive and regression statistics, while qualitative data underwent thematic analysis. Findings revealed that verbal abuse (74.6%), social exclusion (67.5%), physical abuse (59.2%), and unresolved trauma (54.4%) were highly prevalent among respondents. Regression analysis indicated a strong, positive, and significant relationship between traumatic social events and depression (β = 0.221, p < 0.05, p < 0.05). Qualitative narratives from teachers reinforced the statistical results, highlighting the long-term psychological impact of abuse, neglect, and exclusion. The study recommends implementing trauma-informed teacher training, integrating peer-support structures, and establishing accessible school-based mental health services to mitigate the adverse effects of trauma on adolescent mothers.